2021
DOI: 10.3390/ijms22126485
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease (NAFLD) as Model of Gut–Liver Axis Interaction: From Pathophysiology to Potential Target of Treatment for Personalized Therapy

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the leading cause of liver disease worldwide, affecting both adults and children and will result, in the near future, as the leading cause of end-stage liver disease. Indeed, its prevalence is rapidly increasing, and NAFLD is becoming a major public health concern. For this reason, great efforts are needed to identify its pathogenetic factors and new therapeutic approaches. In the past decade, enormous advances understanding the gut–liver axis―the complex network of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 188 publications
0
47
0
Order By: Relevance
“…Although recent studies showed that long-term storage at −80 • C (i.e., up to five years) has limited effects on 16S rRNA sequencing results of human fecal samples [60,61], we do not know how the sample storage may have affected our results, particularly for rare or low-abundance taxa. Finally, due to the bidirectional relation between gut microbiota and NAFLD [62], how the observed microbiota alterations may affect NAFLD development or progression is unclear and needs to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies showed that long-term storage at −80 • C (i.e., up to five years) has limited effects on 16S rRNA sequencing results of human fecal samples [60,61], we do not know how the sample storage may have affected our results, particularly for rare or low-abundance taxa. Finally, due to the bidirectional relation between gut microbiota and NAFLD [62], how the observed microbiota alterations may affect NAFLD development or progression is unclear and needs to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of intestinal dysbiosis characterized a critical event responsible for the impairment of gut-barrier function, becoming a catalyst for metabolic endotoxemia and disruption of multiple metabolic molecular pathways [43]. Over time, studies have focused on the close relationship between the intestine and the liver, introducing the concept of the gut-liver axis involved in the pathogenesis of several disturbances [44][45][46]. Through the portal circulation, intestinal blood and its contents reach the liver, resulting in the induction or progression of liver damage [47].…”
Section: Gut Microbiota and Kupffer Cells Influence On Insulin Resist...mentioning
confidence: 99%
“…As widely reported, GM modulation represents a valid approach to manage many diseases, including NAFLD. In addition to probiotics, prebiotics, symbiotics, and the so-called fecal microbiota transplant (FMT) represent other methods used to restore dysbiosis [ 188 , 189 ].…”
Section: Other Therapeutic Optionsmentioning
confidence: 99%